A REVIEW ON CURRENT MANAGEMENT OF NON-TRAUMATIC SPONTANEOUS INTRACEREBRAL HAEMORRHAGE (World Journal of Current Medical and Pharmaceutical Research, 2019)
Intracerebral haemorrhage is when blood suddenly bursts into brain tissue,causing damage to brain.Intracerebral haemorrhage is an important health problem leading to high rates of death and disability in adults. And it is the most devastating and disabling type of stroke. Uncontrolled hypertension is one of the most common causes for spontaneous intracerebral haemorrhage. Although the number of hospitals for admission for ICH has increased worldwide in past 10 years, mortality has not fallen. Significant treatment approaches include, early diagnosis and haemostasis, aggressive management of hypertension. Factors such as chronic hypertension; cerebral amyloid angiopathy and anticoagulation are commonly associated with intracerebral haemorrhage. Chronic arterial hypertension represents the major risk factor for bleeding. The incidence of hypertension related intracerebral haemorrhage is decreasing in some regions due to improvements of treatments in the chronic hypertension, anti-coagulant related ICH (vitamin-k antagonist and new oral coagulant drugs), represent an increase in the cause of ICH.